Stereological methods based on point counting and unbiased counting frames for two-dimensional measurements in muscles: comparison with manual and image analysis methods - Zacharová, G; Kubínová, L (Journal of muscle research and cell motility, 1995)
Stereological methods, using the principle of point counting and unbiased counting frames, for the estimation of muscle area, total fibre area, number of muscle fibres and mean fibre area are described in detail. Their practical application is demonstrated on cross-sections of the rat soleus muscles. It is shown that the efficiency of these methods is high and their results are comparable with those achieved by the conventional manual and image analysis methods. The main advantages of two-dimensional stereological methods in muscle morphometry are pointed out: measurements are made directly on specimens under the microscope and in the simplest implementation do not require sophisticated and expensive technical equipment. Furthermore, unbiased results are obtained, no segmentation and edge effect problems arise and the quantity of work invested in stereological estimation is reasonable. Based upon the study of the efficiency of used stereological methods, a suitable test system for muscle morphometry is proposed.
Keywords: Bias; Rats; Histological Techniques; kosterní svalová vlákna; Muscle Fibers, Skeletal; zvířata; zkreslení výsledků (epidemiologie); Muscle, Skeletal; kosterní svaly; histologické techniky; myosiny; Myosins; krysa rodu Rattus; Animals